Nada tão fútil que não possa dizê-lo útil: a atividade de consumo na experiência contemporânea - Cristina Petersen Cypriano (2008)
Economic, social and cultural features lay the bases for the understanding of consumption activities. They involve dimensions of life in society that in spite of being intimately connected follow very unique logics. This in turn results in diverse evaluations of the meaning consumption takes in contemporary experience. This study offers a view of the whole that identifies in these perspectives what stands out as most relevant. In order to do this, it brings forth a discussion on the meaning each one attributes to the relationships a consumer establishes with material and symbolic goods, as well as on the ways wherebydifferent points of view understand consumption practices in social interactions. Thus, it is an attempt to discern typical processes in consumption societies and the way they are integrated with the subjective and individual life.